Intramolecular electronic coupling in porous iron cobalt (oxy)phosphide nanoboxes enhances the electrocatalytic activity for oxygen evolution - Zhang, Huabin; Zhou, Wei; Dong, Juncai; Lu, Xue Feng; Lou, Xiong Wen (David) (Energy & environmental science, 2019)
Efficient electrocatalysts are of great importance in improving the water splitting efficiency. Herein, we develop a self-templating strategy to construct porous iron cobalt (oxy)phosphide (Fe-Co-P) nanoboxes as promising pre-catalysts for the oxygen evolution reaction in alkaline solution. The constructed Fe-Co-P nanoboxes exhibit excellent electrocatalytic activity and afford a current density of 10 mA cm −2 at a small overpotential of 269 mV. Moreover, the structural evolution of the metal phosphides in the oxygen evolution process has been well monitored. X-ray absorption near-edge structure analyses and computational studies reveal that the structural merits and the effective intramolecular electronic coupling between the Fe and Co atoms via P/O bridges are responsible for the greatly improved electrocatalytic activity. The effective intramolecular electronic coupling between the Fe and Co atoms via P/O bridges greatly enhances the electrocatalytic activity of Fe-Co (oxy)phosphide nanoboxes.